2019
DOI: 10.36825/riti.07.14.007
|View full text |Cite
|
Sign up to set email alerts
|

Interacción entre el uso y la adicción a las redes sociales y teléfonos móviles entre estudiantes universitarios

Abstract: Resumen: El objetivo del presente estudio es analizar los principales usos de las redes sociales entre hombres y mujeres, de acuerdo con las horas diarias de uso y la conducta adictiva de las redes sociales. Se aplicó un cuestionario de adicción a las redes sociales a una muestra de 466 participantes. Del total, el 60.5% eran mujeres y el 39.5% eran hombres. Se informaron diferencias significativas en el modelo lineal entre los usos principales y el comportamiento adictivo y las horas de uso. Además, se encont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
3
2
0
1
Order By: Relevance
“…It was found that the hours of social media users have a significant indirect relationship to problematic use of social media mediated by the problematic use of the mobile phone. These results are consistent with previous studies (42,43) which concluded that the hours of use are a relevant predictive factor of addictive behavior to social media. These conclusions make sense because in our country mobile phones are the entryway par excellence to the internet, and the web in turn is used mainly to access social media (21).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that the hours of social media users have a significant indirect relationship to problematic use of social media mediated by the problematic use of the mobile phone. These results are consistent with previous studies (42,43) which concluded that the hours of use are a relevant predictive factor of addictive behavior to social media. These conclusions make sense because in our country mobile phones are the entryway par excellence to the internet, and the web in turn is used mainly to access social media (21).…”
Section: Discussionsupporting
confidence: 93%
“…These relationships were considered significant to the final predictive model. Previous studies documented these same results, finding that daily invested hours were an important factor in anticipating problematic use of the mobile phone (42,43).…”
Section: Discussionsupporting
confidence: 61%
“…It is at this point that we talk about social problems related to the use of mobile phones [22], which are complemented by others that are also derived from this excessive use, such as lack of sleep, loss of the notion of time, obsession with what is happening on social networks, or the failure to do other important activities. Despite the fact that this device is used by both genders, some authors report that women spend the most time using it [23].…”
Section: Introductionmentioning
confidence: 99%
“…The problematic use of smartphones and the Internet is closely related to the monitoring of social networks (Rosales & Jasso Medrano, 2019), as these account for the most common channels of communication and interaction among young people. In terms of the effects of COVID-19 on social network use, before the lockdown women showed a more problematic use of social networks than men, in line with different studies (Gómez et al, 2017;Malo-Cerrato et al, 2018;Peris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%